Differentiating services: A study of hotel’s brand image - Syed Alwi, S.F.; Che-Ha, N. (2011)
The current study examines the service brand images of hotels in Malaysia. The attraction and popularity of Malaysia as destination for tourism has created a competitive pressure among servicing sectors particularly the hotel industry to attract and maintain tourist’s loyalty to their hotels. These hotels have, and, are developing competitive marketing strategies to augment their brand images as well as to be seen as the best service provider in the country. However, little is known to understand how these hotels position their service brand images in order to be seen as such. Moreover, with regards to the service sectors, research shows that very few brands have managed to differentiate themselves from their competitors, (McDonald, de Chernatony & Harris, 2001) particularly in hotel industry. Thus, the current study examines the service brand images of hotels in Malaysia.